2023
DOI: 10.3389/fcimb.2023.1167787
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding as a valuable tool for delimiting mollusk species of the genus Biomphalaria Preston, 1910 (Gastropoda: Planorbidae)

Abstract: IntroductionThe genus Biomphalaria in Brazil includes 11 species and one subspecies, three of which are intermediate hosts of Schistosoma mansoni. Due to the recent evolution of this group, some species are difficult to identify based on morphological characters, making the use of genetic markers necessary for species identification. This study aimed to evaluate the use of partial sequences of the cytochrome c oxidase I (coi) gene for the identification of Biomphalaria species using phylogenetic reconstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The snail taxon we identified as B. kuhniana was relatively widely distributed on St. Lucia. It is appropriately cautious to consider our identification of the St. Lucian B. kuhniana specimens as provisional because it is clear from both the literature, 32 , 33 including a recent detailed study by de Araujo et al., 34 and from GenBank entries that B. kuhniana , B. straminea , and B. intermedia are closely related and may best be viewed as a complex of diverging species. Genetic distances between some isolates of provisional B. kuhniana and B. straminea fall in an ambiguous region of < 3% divergence.…”
Section: Discussionmentioning
confidence: 99%
“…The snail taxon we identified as B. kuhniana was relatively widely distributed on St. Lucia. It is appropriately cautious to consider our identification of the St. Lucian B. kuhniana specimens as provisional because it is clear from both the literature, 32 , 33 including a recent detailed study by de Araujo et al., 34 and from GenBank entries that B. kuhniana , B. straminea , and B. intermedia are closely related and may best be viewed as a complex of diverging species. Genetic distances between some isolates of provisional B. kuhniana and B. straminea fall in an ambiguous region of < 3% divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Planorbinae was the most diverse subfamily, consisting of Camptoceratini, Coretini, Drepanotrematini, Helisomatini, Neoplanorbini, Planorbini, and Segmentinini. In recent years, a couple of molecular phylogenetic studies of Planorbidae have been reported, but mainly focused on two economically important genera, i.e., Biomphalaria and Bulinus, that infer the phylogeographic relationship using the mitochondrial gene of cox1 and rrnL, and nuclear gene 18S rDNA, 28 S rDNA and internal transcribed spacer (ITS) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%